2016
DOI: 10.1038/srep28591
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Factors on the Active Substance Production and Antioxidant Activity in Potentilla fruticosa L. and Its Quality Assessment

Abstract: Environmental factors may influence types and contents of active substances. This study investigated the influence of environmental factors on the active substance contents and antioxidant activity of Potentilla fruticosa L. from different regions of China. Also, HPLC fingerprint similarity analysis (SA) coupled with hierarchical cluster analysis (HCA) and discriminant analysis (DA) were further introduced for the accurate classification and quality assessment of P. fruticosa. The results showed that altitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
151
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 55 publications
11
151
0
5
Order By: Relevance
“…Whereas the contents of active principles in Sinapsis alba was reported to have enhanced with increased precipitation as in the present study [25]. Liu et al [22] have however reported that the effect of various environmental factors on the contents of active ingredients varies with the type of the secondary metabolite and on the taxon. Altitude has negative correlation with the contents of tannins and shown positive correlation with the contents of flavonoids and rutin in populations of Potentilla fruticosa collected from different localities in China [22].…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…Whereas the contents of active principles in Sinapsis alba was reported to have enhanced with increased precipitation as in the present study [25]. Liu et al [22] have however reported that the effect of various environmental factors on the contents of active ingredients varies with the type of the secondary metabolite and on the taxon. Altitude has negative correlation with the contents of tannins and shown positive correlation with the contents of flavonoids and rutin in populations of Potentilla fruticosa collected from different localities in China [22].…”
Section: Resultssupporting
confidence: 49%
“…It is well established that biosynthesis of active principles in medicinal plants is largely depends on the environmental conditions [21,22]. Variations found in the contents of curcuminoids in two samples may be due to their two different habitats -Sample A growing in plains, whereas Sample B growing in Western Ghats region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar variations of artemisinin content in relation to stages of negative relationship with the content of tannins in (Liu ., 2016). Annual sunshine also had a positive effect on flavonoids and rutin contents.…”
Section: Podophyllum Hexandrum Et Alsupporting
confidence: 53%
“…Annual sunshine also had a positive effect on flavonoids and rutin contents. Annual mean temperature showed a negative correlation with the accumulation of total phenolics (Liu ., 2016). Likewise, altitude and annual mean temperature were significantly and positively correlated to the contents of chlorogenic acid and flavonoids in (Dong ., 2011); further, the geniposidic acid content showed a significant and positive relationship with the annual sunshine duration but a significant and negative correlation with the annual mean temperature (Dong ., 2011).…”
Section: Podophyllum Hexandrum Et Almentioning
confidence: 99%